The impact of the COVID-19 pandemic on other infections differs by their route of transmission: A retrospective, observational study in Japan. Issue 12 (December 2022) - Komori, Akira; Mori, Hirotake; Naito, Toshio
Abstract: Introduction: The Coronavirus disease 2019 (COVID-19) pandemic and people's subsequent behavioral changes have decreased the cases of respiratory infection worldwide. However, research on infectious diseases with other transmission modes is insufficient. The aim was to assess the impact of the COVID-19 pandemic on non-respiratory infectious diseases: infectious enterocolitis, sexually transmitted diseases such as human immunodeficiency virus (HIV) infection and syphilis, and tick-borne diseases. Methods: This retrospective, cohort study used comprehensive surveillance data from the National Institute of Infectious Diseases in Japan from January 1, 2018, to December 31, 2021. The number of cases of infectious diseases before the COVID-19 pandemic (2018–2019) was compared with that during the COVID-19 pandemic (2020–2021). Reduction rates were calculated as the number of disease cases during the COVID-19 pandemic in 2020 and 2021, respectively, divided by the mean number of disease cases in 2018 and 2019. Results: The total numbers of cases of infectious enterocolitis, sexually transmitted diseases, and tick-borne diseases during the study period were 2, 507, 304 cases, 24, 972 cases, and 3012 cases, respectively. The number of cases decreased for infectious enterocolitis and sexually transmitted diseases during the COVID-19 pandemic compared with before the COVID-19 pandemic, with an approximately 40–50% decrease in enterocolitis and 30–55% decreases in sexually transmitted diseases. However, cases of tick-borne diseases changed little, with a 0.2% increase in 2020 and a 6% increase in 2021. Conclusion: The COVID-19 pandemic had a different impact on the number of cases of infectious diseases depending on their mode of transmission.